Teorija mentalnih modelov v raziskovanju pogovora - Verdonik, Darinka (Jezik in slovstvo, 2011)
The article deals with the question of whether it is possible to establish a theoretical framework for the research of conversation that would include sociological, cognitive and linguistic aspects of discourse, and would consequently provide a comprehensive explanation of conversation. The point of departure is the socio-cognitive model of Walter Kintsch and Teun A. van Dijk, which is based on the theory of mental models. In the article, the advantages and disadvantages of this model for the comprehensive analysis of conversation are discussed.
Keywords: kognitivna lingvistika; pogovor; kogntivna analiza diskurza; mentalni modeli pogovora; socio-kognitivni model pogovora